Islamic Banking and Halal MSME Development: Financial Access and Inclusion - Ahyar, Muhammad Khozin; Catur Kurniawan; Dimas Riski Efendi; M Ramli (Journal of Finance and Islamic Banking, 2024)
This study examines the accessibility of MSME financing in Islamic banks, focusing on the transformations accelerated by the Covid-19 pandemic. As community activities were restricted, Islamic banks rapidly digitized their services to maintain customer engagement. Despite digital advancements, financing processes, especially for MSMEs, still heavily rely on face-to-face interactions, which pose challenges for MSME clients with limited access to information, capital, and guarantees. Using a quantitative approach with SmartPLS, the research investigates the impact of various financial inclusion indicators on MSME financing. The outer model test confirmed the validity and reliability of all variables (AVE > 0.50, Cronbach’s Alpha > 0.75). The inner model test revealed that office networks and IRDPK significantly influenced MSME financing, while ATM availability showed a moderate effect. Additionally, the IRPBY variable did not exert a positive impact. This study highlights the crucial role of Islamic bank office networks in facilitating MSME access to financing, especially in the halal sector, and suggests that further digital innovations could enhance accessibility.